Exploring the Potential of Fish Gelatin and Sustainable Alternatives in the Food Industry: A Comprehensive Analysis - Nabeel Ahmad, Jayashree M kudari, Shweta Singh (Revista Electronica de Veterinaria, 2024)
Gelatin, a frequently used dietary component is produced by heat denaturing and hydrolyzing animal collagen. However, nutritional limitations associated with pig gelatin, driven by cultural and religious reasons and worries about zoonotic infections in cattle, have motivated the search for alternate gelatin sources. Despite obstacles linked to their gelling characteristics compared to human Gelatin, Fish and Fish metabolites have emerged as desirable alternatives. This study investigates the possibilities of fish gelatin and explores renewable options in the food business. PRISMA was used to assess the strength of the gel measurements of the fish gelatin from warm- and cold-water environments compared to human Gelatin to determine their adequacy as a substitute. We included a total of 15 studies after an examination of the strength of the gel and the extraction measurement techniques. The investigation found that the mean gel thickness Gelatin made from fish, including warm-water and cold-water variants, was substantially lower than that of human Gelatin. This indicates that fish skin gelatin from warm water performs similarly to human Gelatin in terms of gel formation ability, suggesting that it might be a good alternative for manufacturing food gels.The study investigates the variations in Fish and mammalian gelatin gels' melting and gelling temperatures and their structural characteristics from sole to composite gel. It highlights the necessity of researching different gelatin sources and substituting proteins to solve environmental issues and satisfy the rising demand for sustainably produced foods.